Situational Method Engineering - Henderson-Sellers, Brian; Ralyté, Jolita; Ågerfalk, Pär J.; Rossi, Matti; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
While previously available methodologies for software – like those published in the early days of object technology – claimed to be appropriate for every conceivable project, situational method engineering (SME) acknowledges that most projects typically have individual characteristics and situations. Thus, finding the most effective methodology for a particular project needs specific tailoring to that situation. Such a tailored software development methodology needs to take into account all the bits and pieces needed for an organization to develop software, including the software process, the input and output work products, the people involved, the languages used to describe requirements, design, code, and eventually also measures of success or failure. The authors have structured the book into three parts. Part I deals with all the basic concepts, terminology and overall ideas underpinning situational method engineering. As a summary of this part, they present a formal meta-model that enables readers to create their own quality methods and supporting tools. In Part II, they explain how to implement SME in practice, i.e., how to find method components and put them together and how to evaluate the resulting method. For illustration, they also include several industry case studies of customized or constructed processes, highlighting the impact that high-quality engineered methods can have on the success of an industrial software development. Finally, Part III summarizes some of the more recent and forward-looking ideas. This book presents the first summary of the state of the art for SME. For academics, it provides a comprehensive conceptual framework and discusses new research areas. For lecturers, thanks to its step-by-step explanations from basics to the customization and quality assessment of constructed methods, it serves as a solid basis for comprehensive courses on the topic. For industry methodologists, it offers a reference guide on features and technologies to consider when developing in-house software development methods or customising and adopting off-the-shelf ones.
Part I SME Basics -- Chapter 1 Introduction -- Chapter 2 Method chunks, method fragments and method components -- Chapter 3 Method Engineering as a Social Practice -- Chapter 4 Formal descriptions -- Part II Applying SME in Practice -- Chapter 5 Identification and construction of individual method chunks/fragments -- Chapter 6 Processes for creating a methodology from method parts -- Chapter 7 Tailoring a constructed method -- Chapter 8 Assessing quality -- Chapter 9 Examples of constructed processes -- Part III The Future of SME -- Chapter 10 Recent advances in SME -- Chapter 11 Final summary and future work.
Keywords: Software engineering; Management information systems; Computer science; Software Engineering; Management of Computing and Information Systems